Bound state solutions for quasilinear Schrödinger equations with Hardy potential - Yanfang Xue; Wenjing Gu; Jianxin Han (Results in Applied Mathematics)
This paper is concerned with the existence of bound state solutions for quasilinear Schrödinger equations with Hardy potential and Berestycki–Lions type conditions. By using the variational methods, we get the existence results which is a complement to the ones in Hu et al. (2022).